Taste disorders due to unilateral upper molar extraction in juvenile and adult albino rats - A. Gutiérrez-Patiño Paúl; E. Aguirre-Siancas (Neurology Perspectives, 2025)
Introduction: The sense of taste is fundamental to life; some studies have revealed a link between dental deafferentation (DD) by upper molar extraction and taste abnormalities in rats. However, no studies have been found that evaluate these variables using the Taste Reactivity Test (TRT). Methods: Forty male Wistar rats (20 juveniles and 20 adults) were used and assigned to a control and experimental group. Both groups were fitted with cannulae for TRT, while rats in the experimental group also had their right upper molars extracted. Using an ingestive solution (1 M sucrose) and an aversive solution (3 mM denatonium benzoate [BD]), TRT was performed on days 1, 7, 14, and 21. Body and orofacial reactions were recorded and scored. Results: DD influences ingestive responses in juvenile rats at days 7, 14, and 21; however, it only affects aversive responses at day 21. In adult rats, it influences ingestive responses at days 14 and 21, although it only affects aversive responses at day 14. When comparing ingestive and aversive responses between juvenile and adult rats in the experimental group, differences were identified in ingestive responses at days 7 and 14. Conclusions: In juvenile and adult rats, upper molar extraction has a negative influence on ingestive and aversive responses. In addition, compared to adult rats, it has a negative effect on ingestive responses in juvenile rats. Resumen: Introducción: El sentido del gusto es fundamental para la vida, algunos estudios han revelado un vínculo entre la desaferentación dental (DD) mediante exodoncia de molares superiores en ratas y anomalías del gusto. Sin embargo, no se han encontrado trabajos que evalúen estas variables mediante el test de reactividad gustativa (TRG). Métodos: Se utilizaron 40 ratas Wistar machos, 20 jóvenes y 20 adultos, en cada categoría asignadas a un grupo control y experimental. A ambos grupos se les colocaron cánulas para TRG, mientras que a las ratas del grupo experimental se les extrajo los molares superiores derechos. Utilizando una solución ingestiva (sacarosa 1 M) y una aversiva (benzoato de denatonio [BD] 3 mM), se realizó el TRG los días 1, 7, 14 y 21. Se registraron y calificaron las reacciones corporales y orofaciales. Resultados: La DD influye en las respuestas ingestivas en ratas jóvenes a los 7, 14 y 21 días; en cambio solo afecta las respuestas aversivas el día 21. En ratas adultas influye en las respuestas ingestivas a los 14 y 21 días; aunque solo afecta las respuestas aversivas el día 14. Al contrastar las respuestas ingestivas y aversivas entre ratas jóvenes y adultos de los grupos experimentales se identificó diferencias en las respuestas ingestivas los días 7 y 14. Conclusiones: En ratas jóvenes y adultas, la DD tiene una influencia negativa sobre las respuestas ingestivas y aversivas. Además, en comparación con las ratas adultas, tiene un efecto negativo sobre las respuestas ingestivas de las ratas jóvenes.